European Technological Sovereignty: An Emerging Framework for Policy Strategy - Francesco Crespi; Serenella Caravella; Mirko Menghini; Chiara Salvatori (Intereconomics, 2021)
The COVID-19 crisis has revealed the deep technological and production dependencies of the EU on third countries in sectors deemed as particularly strategic and has thus fuelled the debate on (the lack of) European technological sovereignty in critical fields. This article argues that in the light of a renewed interest in relaunching a European industrial policy, technological sovereignty considerations must be fully incorporated into policy objectives and instruments.
Keywords: 330